Interspecific interactions explain variation in the duration of paternal care in the burying beetle. (November 2015) - De Gasperin, Ornela; Duarte, Ana; Kilner, Rebecca M.
Abstract : Why is there so much variation within species in the extent to which males contribute to offspring care? Answers to this question commonly focus on intraspecific sources of variation in the relative costs and benefits of supplying paternal investment. With experiments in the laboratory on the burying beetle, Nicrophorus vespilloides, and its phoretic mite Poecilochirus carabi, we investigated whether interactions with a second species might also account for intraspecific variation in the extent of paternal care, and whether this variation is due to adaptation or constraint. In our first experiment we bred beetles in the presence or absence of phoretic mites, using a breeding box that mimicked natural conditions by allowing parents to leave the breeding attempt at a time of their choosing. We found that males abandoned their brood sooner when breeding alongside mites than when breeding in their absence. Female patterns of care were unchanged by the mites. Nevertheless, in this experiment, no correlates of beetle fitness were affected by the presence of the mites during reproduction (neither paternal life span after reproduction nor brood size or average larval mass). In a second experiment, we again bred beetles with or without mites but this time we prevented parents from abandoning the brood. This time we found that both parents and the brood suffered fitness costs when breeding alongside mites, compared with families breeding in the absence of mites. We conclude that males adaptively reduce their contributions to care when mites are present, so as to defend their offspring's fitness and their own residual fitness. Interspecific interactions thus account for intraspecific variation in the duration of paternal care. Highlights: The extent of paternal care varies greatly within species. Some of this variation might be due to interspecific interactions. We investigated how mites influence paternal care in the burying beetle. We found that males leave their brood earlier when mites are present. We show that this is adaptive because it enhances offspring fitness.